High-frequency stimulation of the subthalamic nucleus induces a sustained inhibition of serotonergic system via loss of cell phenotype - Faisal Alosaimi; Yasin Temel; Sarah Hescham; Victoria S. Witzig; Faris Almasabi; Sonny K. H. Tan; Ali Jahanshahi (Scientific Reports, 2022)
Abstract Deep brain stimulation (DBS) of the subthalamic nucleus (STN) has become a standard treatment for Parkinson’s disease (PD). However, in a considerable number of patients debilitating psychiatric side-effects occur. Recent research has revealed that external stimuli can alter the neurotransmitters’ homeostasis in neurons, which is known as “neurotransmitter respecification”. Herein, we addressed if neurotransmitter respecification could be a mechanism by which DBS suppresses the serotonergic function in the dorsal raphe nucleus (DRN) leading to mood changes. We infused transgenic 5-HT-Cre (ePET-Cre) mice with AAV viruses to achieve targeted expression of eYFP and the genetically encoded calcium indicator GCaMP6s in the DRN prior to methyl-4phenyl-1,2,3,6-tetrahydropyridine (MPTP) treatment. Mice received bilateral DBS electrodes in the STN and an optic fiber in the DRN for calcium photometry. MPTP-treated mice demonstrated behavioral and histological PD phenotype, whereas all STN-DBS animals exhibited an increased immobility time in the forced swim test, reduced calcium activity, and loss of tryptophan hydroxylase-2 expression in the DRN. Given the prominent role of calcium transients in mediating neurotransmitter respecification, these results suggest a loss of serotonergic phenotype in the DRN following STN-DBS. These findings indicate that loss of serotonergic cell phenotype may underlie the unwanted depressive symptoms following STN-DBS.